2017
DOI: 10.1159/000468150
|View full text |Cite
|
Sign up to set email alerts
|

Search for Internal Cancers in Mice Tattooed with Inks of High Contents of Potential Carcinogens: A One-Year Autopsy Study of Red and Black Tattoo Inks Banned in the Market

Abstract: Background and Objective: Tattoo ink stock products often contain potential carcinogens, which on large-scale population exposure may be clinically relevant. The aim of this autopsy study in mice was to screen major organs for clinical and subclinical cancers. Methods: Mice were tattooed on their backs. In total, 48 mice were included and divided into 4 groups; 11 mice tattooed black, 10 tattooed red, and 5 mice serving as untreated controls. A group of 22 mice with black tattoos and exposed to ultraviolet rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(22 reference statements)
0
3
0
3
Order By: Relevance
“…After our mice were euthanized, autopsies were performed and reported in a separate study by Sepehri et al [20] No cancers in internal organs were found in red (or black)-tattooed mice neither macroscopically nor by systematic microscopy of the organs. [20] It was also documented that deposits originating from red (and black) tattoos were observed in the liver, in the Kupffer cells, by electron microscopy. [21] The internal organs of highest exposure were the lymph nodes and the liver.…”
Section: Discussionmentioning
confidence: 78%
“…After our mice were euthanized, autopsies were performed and reported in a separate study by Sepehri et al [20] No cancers in internal organs were found in red (or black)-tattooed mice neither macroscopically nor by systematic microscopy of the organs. [20] It was also documented that deposits originating from red (and black) tattoos were observed in the liver, in the Kupffer cells, by electron microscopy. [21] The internal organs of highest exposure were the lymph nodes and the liver.…”
Section: Discussionmentioning
confidence: 78%
“…Der Nachweis von PAH in vivo konnte in den wesentlichen Organen der Exkretion und des Metabolismus wie der Leber, Milz und Niere noch nicht erbracht werden. In Anbetracht der hohen Konzentrationen von PAH in der Tinte und der deutlich erniedrigten Werte in der Dermis und in den Lymphknoten kann angenommen werden, dass eine große Menge metabolisiert, ausgeschieden und abtransportiert wird [16,17]. Im Rahmen der Elimination über den Lymph-und Blutflussweg erfolgt mit anderen Organen entsprechender Kontakt, und daraus resultiert eine mögliche Interaktion [4].…”
Section: » Pah Können Apoptose Auslösen Und Oxidativen Stress Induzierenunclassified
“…Die oftmals herangezogenen freien Konzentrationen von potenziell toxischen Elementen entsprechen nicht jenen im Körper, die durch den Metabolismus und die Ausscheidung modifiziert werden [17,25].…”
Section: Potenzielle Induktion Der Kanzerogenitätunclassified
See 1 more Smart Citation
“…The maximum permitted concentrations of carcinogenic, mutagenic and reproduction-toxic substances in tattoo inks were established, and 2. The necessary conditions for risk evaluation prior to performing tattoos and for the appropriate information of customers about the health risks of the latter were described [2,32,36].…”
Section: Dermatology Online Journal || Case Presentationmentioning
confidence: 99%